Quantum-Safe Encryption Schemes Based on Hadamard Code - Rai P.; Singh B.; Gupta A.J. (My University, 2025)
In this article, we design some public-key encryption schemes using various frameworks like McEliece, Niederreiter, HyMES, and a new framework proposed by Ivanov et al. taking Hadamard code as secret code. We provide key generation, encryption, and decryption algorithms and also give toy examples to illustrate these algorithms. We discuss various attacks and also implement all these encryption schemes in SageMath software. © The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2024.